Deteksi Jamur Penyebab Onychomycosis Pada KukuKaki Penghuni Lembaga Pemasyarakatan Perempuan Kelas IIA Sungguminasa: Detection Of Fungus Causing Onychomycosis In Toenails Of Class Iia Sungguminasa Women’s Penitentiary - Laganda, Berliani; Hartati; Thaslifa, Thaslifa (Fakultas Kesehatan Masyarakat Universitas Dayanu Ikhsanuddin, 2023)
ABSTRACT Onychomycosis is an infection of the nails caused by fungus. The growth of fungus on nails can be influenced by several others factors, personal hygiene, the humidity level of the surrounding environment, and contact with a source of infection. Penitentiary institutions have high humidity levels because the air ventilation is very minimal, so there is a high risk of causing inmates to experience fungal infections of the nails. The research aims to detect the fungus that causes onychomycosis in prisoner’s nails. The research was descriptive in nature, consisting of 8 samples of prisoner nail scrapings obtained by using a purposive sampling technique and examined in the Microbiology laboratory at the Faculty of Medicine, Hasanuddin University. The examination method used the potassium hydroxide (KOH) method which showed that there were fungal hyphae in 3 samples and continued with the culture method. The culture results illustrate the presence of the fungus that caused onychomycosis, namely Candida sp. and Trichophyton rubrum. Prisoners were expected to pay attention and to improve their personal hygiene. Keywords : Correctional Institutions, Prisoners, Onychomycosis